2021
DOI: 10.1136/bmjopen-2021-054756
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a customised mobile phone text messaging intervention supported by data from activity monitors for improving lifestyle factors related to the risk of type 2 diabetes among women after gestational diabetes: protocol for a multicentre randomised controlled trial (SMART MUMS with smart phones 2)

Abstract: IntroductionGestational diabetes (GDM) contributes substantially to the population burden of type 2 diabetes (T2DM), with a high long-term risk of developing T2DM. This study will assess whether a structured lifestyle modification programme for women immediately after a GDM pregnancy, delivered via customised text messages and further individualised using data from activity monitors, improves T2DM risk factors, namely weight, physical activity (PA) and diet.Methods and analysisThis multicentre randomised contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…These results support the clinical utility of the DeMpower app as a home digital patient empowerment and communication tool that might help patients achieve glycemic control that is independent of the antidiabetic treatment. Similarly, previous studies have also shown the benefits of home-based digital patient empowerment tools in the control of T2DM [23][24][25][26][27][28][29][30][31][32][33][43][44][45][46][47]. For example, the ValCrónic study [30] showed that the proportion of people with HbA 1c ≥8% decreased significantly (by 44%) after 1 year of telemonitoring.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…These results support the clinical utility of the DeMpower app as a home digital patient empowerment and communication tool that might help patients achieve glycemic control that is independent of the antidiabetic treatment. Similarly, previous studies have also shown the benefits of home-based digital patient empowerment tools in the control of T2DM [23][24][25][26][27][28][29][30][31][32][33][43][44][45][46][47]. For example, the ValCrónic study [30] showed that the proportion of people with HbA 1c ≥8% decreased significantly (by 44%) after 1 year of telemonitoring.…”
Section: Discussionmentioning
confidence: 70%
“…In fact, effective diabetes self-management is a key goal, but it should be measured and monitored as part of routine care and technology may help patients and guide clinical decisions [22]. Different studies have shown that the use of telemedicine is associated with improvements in patients' outcomes such as adherence, pathology control, and engagement [21,[23][24][25][26][27]. However, in Spain, there are few studies evaluating eHealth solutions for people with T2DM, mostly developed in small local settings [28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Identifying at‐risk women early, at a point where their future risk is modifiable through screening for diabetes and cardiovascular risk among women with GD, is one such potential approach. Better messaging to improve awareness, electronic decision support in primary care, reminders and incentivisation of women post partum are all possible interventions 26 that could help prevent the longer‐term risks of diabetes and CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Breastfeeding support programs are effective to improve breastfeeding and generally acceptable to women [ 33 ]. However, minimal research has integrated lifestyle programs with breastfeeding support interventions aimed at reducing type 2 diabetes risk [ 34 ]. A recent Cochrane Review found that at least 4–8 postpartum lactation support contacts were required to improve breastfeeding rates.…”
Section: Discussionmentioning
confidence: 99%